2022
DOI: 10.58968/isf.v2i1.133
|View full text |Cite
|
Sign up to set email alerts
|

How Far Has Zakat Efficiency been Researched?

Abstract: This study aims to determine research trends regarding zakat efficiency topic, assess research collaboration relationships, and identify future research directions. The 52 sample articles published between 2011-2022 on zakat efficiency analyzed by qualitative and quantitative approaches, namely Bibliometric and Systematic Literature Review (SLR) methods. This research uses VosViewers software. It is known that the four sub-themes that dominate research related to zakat efficiency are: Collection and distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Next, a text analysis of bibliometrix mapping results related to "word" will be conducted. Other studies using bibliometric analysis for the example can be seen at Uula & Ikhwan (2022), Nasution et al, (2022), Maulida & Ali (2023), Uula & Maziyyah (2022), and also Puspita (2023).…”
Section: Methodsmentioning
confidence: 99%
“…Next, a text analysis of bibliometrix mapping results related to "word" will be conducted. Other studies using bibliometric analysis for the example can be seen at Uula & Ikhwan (2022), Nasution et al, (2022), Maulida & Ali (2023), Uula & Maziyyah (2022), and also Puspita (2023).…”
Section: Methodsmentioning
confidence: 99%
“…The sampling technique used in this research is purposive non-probability sampling method, which aims to fulfill certain information in accordance with the desired research objectives. Research using bibliometric analysis for the example can be found at Niswah (2020), Izza (2022), Ikhwan (2021), Muadzah (2022), Riani (2021), Uula & Maziyyah (2022), As-Salafiyah (2022), Sari (2022), and Uula (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Several similar studies on the topic of Islamic economics and finance, for example, are studies conducted by Niswah (2020), Ruhana (2021), Riani & Fatoni (2022), Izza et al, (2021), Putri (2022), Uula & Maziyyah ( 2022) and Sari (2022). Based on the results of the initial search analysis in conducting an analysis of the metadata collected and obtained after running the search query, information and general descriptions regarding research articles with the keyword "takaful efficiency" are obtained.…”
Section: Methodsmentioning
confidence: 99%